68.9k views
5 votes
The midpoint of ab =

The midpoint of ab =-example-1
User Sigcont
by
5.5k points

2 Answers

7 votes

Answer:

(0, 0)

Explanation:

(-2, -2) is point B.

(2, 2) is point A.

The center or midpoint of the line is:

(x1 + x2)/2 , (y1 + y2)/2

(2+-2)/2 , (-2+2)/2

0/2, 0/2

0, 0

User Taylor Riggan
by
5.6k points
2 votes

Answer:

M(x,y) = (0,0)

Explanation:

The endpoints are (2,2) and (-2,-2)

Let's find the midpoint now

=> M(x,y) =
((x1+x2)/(2), (y1+y2)/(2))

=> M(x,y) =
((2-2)/(2) ,(2-2)/(2))

=> M(x,y) =
((0)/(2) , (0)/(2) )

=> M(x,y) = (0,0)

User Tim Ferrell
by
5.2k points